2012
DOI: 10.1177/070674371205700707
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Guidelines for Bipolar Disorder: Practical Issues in Long-Term Treatment with Lithium

Abstract: Objective: Several treatment guidelines are available for clinicians working with patients with bipolar disorder (BD), but some of the more nuanced aspects of lithium therapy go beyond the scope of such guidelines. Therefore, in this perspective, our objective was to focus on specific practical issues of lithium treatment, including the selection and initiation of long-term treatment, and management and discontinuation (if indicated) of lithium prophylaxis. Method:We conducted a focused review of the relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 93 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…BD can cause circadian rhythm disturbances (Gonzalez, 2014), cognitive impairment, verbal memory loss (Cardoso et al, 2015), and increase the risk of other diseases. Suicide (Calkin and Alda, 2012) is the leading cause of death in BD patients. In one long-term study, the average suicide rate of major emotional patients was 15–20%, and while BD patients had a rate of more than 20% (Pompili et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…BD can cause circadian rhythm disturbances (Gonzalez, 2014), cognitive impairment, verbal memory loss (Cardoso et al, 2015), and increase the risk of other diseases. Suicide (Calkin and Alda, 2012) is the leading cause of death in BD patients. In one long-term study, the average suicide rate of major emotional patients was 15–20%, and while BD patients had a rate of more than 20% (Pompili et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it accumulates in marine animals, algae and vegetables which represent the primary dietary Li sources and may contribute from 66% to 90% of the total Li intake (Curran and Ravindran 2014;McCartney et al 2014). Lithium carbonate has been used as an invaluable drug to cure bipolar disorders and manic-depressive illness for more than 60 years (Grunze et al 2010;Calkin and Alda 2012;Vieta and Valenti 2013). Moreover, it was reported that this drug used as chronic treatment to prevent development of Alzheimer's disease (Forlenza et al 2011) and for treatment of refractory depression (Edwards et al 2013;Cleare et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other predictors of a favorable response to lithium recognized elsewhere in the literature include long depression-free intervals, absence of rapid cycling or comorbid substance and alcohol issues [116], a family history of lithium responders [117] and low comorbidities [10]. Greater illness severity predicts a poorer response to lithium during the maintenance phase [118].…”
Section: Predictors Of Response To Lithium Therapymentioning
confidence: 97%
“…Lack of industry research and funding due to the absence of a patent [1,8] may also have contributed to its decline. Furthermore, the expansion of the bipolar diagnosis and acceptance of 'bipolar spectrum disorders' may have resulted in lithium appearing less effective due to the increase in patients with atypical features who are less likely to respond to lithium [10].…”
Section: Abstract: Bipolar Disorder • Dosing • Efficacy • Lithium • Pmentioning
confidence: 99%